2021
DOI: 10.5696/2156-9614-11.30.210611
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Level of Rare Earth Element Contamination of Atmospheric Dust in Nigeria

Abstract: Background. Rare earth element (REE) composition of atmospheric dust has recently been used to trace potential sources of dust pollution. Objective. The present study aimed to determine the sources of atmospheric pollution in the study area using REE patterns and determine their level of pollution. Methods. Twenty-five (25) atmospheric dust samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
(54 reference statements)
1
2
1
Order By: Relevance
“…Generally, the sources of Ga, La, Li, Rb, and Sc sources are also similar. They are either released from weathering minerals and rocks, as by-products in industrial processes, or from waste products [73][74][75][76]. The results of our study reflect the same close relationship between these metals.…”
Section: Discussionsupporting
confidence: 72%
“…Generally, the sources of Ga, La, Li, Rb, and Sc sources are also similar. They are either released from weathering minerals and rocks, as by-products in industrial processes, or from waste products [73][74][75][76]. The results of our study reflect the same close relationship between these metals.…”
Section: Discussionsupporting
confidence: 72%
“…Anthropogenic enrichment of REE has also been linked to proximity to intense agricultural practices and the application of phosphate-based fertilizers, but the enrichment of REE has also been associated with regions near to polluted sites such as large cities, e-waste dump sites, and industrial centers (Balaram 2019). Dust has also been identi ed as a major atmospheric source of REE deposition (Kolawole et al 2021). In this study, while some cores exhibited slight enrichment, we found little evidence of substantial enrichment of REE's in our global peatland dataset, and there was only one case were EF exceeded 10 suggesting any contamination is likely localized to sources or any recent increases in REE deposition are not captured in the 10-20 cm depth of peat.…”
Section: Global Metal Enrichment Patterns In Bog and Fen Peatlandscontrasting
confidence: 54%
“…Even higher REE levels were found in atmospheric dust from the city of Ibadan (Nigeria), ranging from 42.5 μg g −1 (residential) to 785 μg g −1 (industrial), with mean ΣREE levels in industrial, transportation, landfill, residential, remote areas, and local soil of 638, 283, 130, 163, 96.0, and 144 μg g −1 . The average ΣREE content in dust in industrial and transportation areas was about 4.5 and 2.0 times higher than the average ΣREE content in soil, respectively (Kolawole et al, 2021). The main sources of…”
Section: Airmentioning
confidence: 86%
“…Concentrations exceeding the recommended limits set by AAQCs (2012) are often found near mining and industrial areas (Tracy and Meyerhof, 1967;Shaltout et al, 2013;Wang et al, 2014;Dai et al, 2016;Wang et al, 2016;Hussein et al, 2018;Fesenko and Emlutina 2021;Kolawole et al, 2021), Table 3. For example, U concentrations of 2-200 ng m −3 have been measured within 2 km of a refinery (Tracy and Meyerhof, 1967), which exceeds the recommended limits by a factor of 6.…”
Section: Airmentioning
confidence: 99%